The impact of Dynamic Capability and Innovation Capability on Competitive Advantage - Masoumeh Hoseinzadeh Shahri; Sahebeh Shahini (کاوش‌های مدیریت بازرگانی, 2018)
Due to its highly changing nature and variety, competition nowadays requires capabilities that can provide competitive advantages for firms. The purpose of this research is to investigate the effect of dynamic capabilities and innovation capabilities on competitive advantage. Sensing, learning, integration, coordination and reconfigured capabilities are taken into account as the dynamic capabilities, and exploitation and exploration capabilities were taken into account as the innovation capabilities. As for competitive advantage, three dimensions including cost leadership, differentiation and focus strategy were taken into consideration. The sample consisted of 217 companies which manufactured heating and cooling systems in Tehran. They were selected by Sampling Available. The research is an applied study and, in terms of data collection, it is a descriptive and correlational study. To analyze the data, the structural equation model was used. PLS measurement, correlation test, mean comparison of one group and comparison of the mean of two independent groups were conducted too. The findings indicate that, to achieve a cost leadership strategy, all the dimensions of dynamic capabilities are of positive and significant effects. However, to reach the differentiation strategy, only the sensing capability has a positive and significant effect, and both dimensions of innovation capability have a positive and significant effect on the dimensions of competitive advantage.